ANALISIS IMPLEMENTASI PEMBIAYAAN MIKRO SYARIAH DALAM PENGEMBANGAN USAHA MIKRO PADA BANK SYARIAH INDONESIA KCP MEDAN AKSARA - Nadya Ervina; Yenni Samri Juliati Nasution; Muhammad Lathief Ilhamy Nasution (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
This study examines how Sharia Micro KUR Financing operates at BSI KCP Medan Aksara and how Micro KUR Financing plays a role in micro business development. This research is qualitative descriptive and involves observation, documentation and interviews. According to research, Sharia Micro KUR Financing at BSI KCP Medan Aksara works well and has no problems. Investments are made accurately, which solves any problem. Sharia Micro KUR financing has the ability to solve capital problems, which is important for business development. They play an important role in keeping micro-businesses flowing, revenue growth and funds flowing, and they have the ability to grow businesses for many clients.